Diurnal Rhythm of Muscular Strength Depends on Temporal Specificity of Self-Resistance Training. Issue 3 (March 2016) - Zbidi, Sana; Zinoubi, Badrane; Vandewalle, Henry; Driss, Tarak
Abstract : Abstract: Zbidi, S, Zinoubi, B, Vandewalle, H, and Driss, T. Diurnal rhythm of muscular strength depends on temporal specificity of self-resistance training. J Strength Cond Res 30(3): 717–724, 2016—The study investigated the effect of the time-of-day at which maximal isometric voluntary co-contraction (MIVCC) training is conducted on the adaptation and diurnal variation of maximal and explosive force production. Twenty active men underwent a 6-week (3 times per week) MIVCC training of the right elbow joint. The participants were randomly assigned to a morning training group (MTG, 07:00–08:00 hours) and evening training group (ETG, 17:00–18:00 hours). The maximal voluntary force (MVF) and maximal rate of force development (MRFD) during isometric elbow flexion (MVFF and MRFDF ) and extension (MVFE and MRFDE ) were recorded before (T0) and after (T1) training in the morning and evening. At T0, MVF and MRFD were higher in the evening compared with those in the morning for the MTG and ETG ( p ⩽ 0.05). At T1, MVFF and MVFE increased in the morning and evening for both groups ( p < 0.001). The MRFDF and MRFDE increased only if training and test session were scheduled at the same time. The relative increase of MVF was greater at the specific time of training for the MTG (12 and 17.6% in MVFF and MVFE, respectively) and ETG (9.8 and 13.4% in MVFF and MVFE, respectively). The diurnal variations in MVF and MRFD during flexion and extension disappeared in the MTG and persisted in the ETG. Maximal isometric voluntary co-contraction training enhanced muscle strength whatever the time-of-day at which the training was scheduled without alteration of explosive force. In contrast, to optimize the muscle strength, our results suggested that morning training may be accompanied by the greatest muscle strength gain and blunted muscle strength variation observed between the morning and evening.